TREND OF USING SITUATIONAL JUDGEMENT TEST ON SCHOOL TEACHERS: A SYSTEMATIC LITERATURE REVIEW - Nadmilail, Azad Iqram; Matore, Mohd Effendi Ewan Mohd (The journal of contemporary issues in business and government, 2021)
Situational Judgement Tests (SJTs) have become progressively famous instruments that have been utilized in various fields, especially for personnel selection, promotion, and recruitment. There have been several research studies conducted on school teachers. However, there is an absence of attention in such studies regarding the analysis of the country-of-origin and time trends of SJTs in research. This review will turn out to be more gainful for the educational researcher to enhance their insight and comprehension of the research trend for further studies. Hence, this study aims to review country-of-origin trends and time trends of SJTs research on school teachers. This study employed a Systematic Literature Review (SLR) as a research method which comprises a review protocol that specifies the topic to be investigated and the method customized in conducting the review. It has significant benefits to detect relevant literature review and how information is acquired from the primary study. Planning, conducting, and reporting the review are phases of the SLR method. This study found that the SJTs on school teachers are most widely utilized in European countries and have grown dramatically by 27.78 percent for over the past ten years throughout the world. This study recommends several active researchers as an expert and their research practices that can be referred to. Detailed empirical studies should be conducted to see the purpose of the studies practiced and the characteristics of the attributes and competencies being measured. Sifting articles can be improved the research by using non-common languages, utilizing a more extensive database, and exploring other research features through in-depth research.